2020
DOI: 10.5114/reum.2020.95359
|View full text |Cite
|
Sign up to set email alerts
|

Serum chemerin and visfatin levels and their ratio as possible diagnostic parameters of rheumatoid arthritis

Abstract: Objectives: Rheumatoid arthritis (RA) is a chronic inflammatory disease affecting the synovium and articular cartilage that initiates joint damage. Rheumatoid arthritis is associated with a change in many inflammatory biomarkers. The present study aims to examine the diagnostic ability of inflammatory adipocytokines (chemerin and visfatin) and their ratio for RA disease. Material and methods: The study recruited 60 RA patients and 30 healthy controls. Serum visfatin and chemerin were measured using the ELISA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…In early RA patients managed using the treat to target strategy, Tolusso et al identified that chemerin levels can be considered a predictor of early remission of inflammation [17]; however, other studies are required to validate these findings. These data published in the literature support the hypothesis that chemerin levels are related to disease activity in RA [11,15,18]. Nevertheless, there are no previous studies assessing the relation between the persistence of disease activity in RA patients treated with DMARDs and serum chemerin levels.…”
Section: Introductionsupporting
confidence: 77%
“…In early RA patients managed using the treat to target strategy, Tolusso et al identified that chemerin levels can be considered a predictor of early remission of inflammation [17]; however, other studies are required to validate these findings. These data published in the literature support the hypothesis that chemerin levels are related to disease activity in RA [11,15,18]. Nevertheless, there are no previous studies assessing the relation between the persistence of disease activity in RA patients treated with DMARDs and serum chemerin levels.…”
Section: Introductionsupporting
confidence: 77%
“…Cleaved chemerin isoforms are increased in RA synovial fluid [ 34 ], and elevated chemerin plasma levels are correlated with BMI and disease activity in RA [ 79 , 80 ]. Recently, it has been postulated that visfatin and chemerin are increased in RA patients and chemerin can be used as an inflammation marker for RA patients [ 81 ]. Interestingly, total chemerin was found to be increased in RA serum, although it was recently revealed using a proteomics approach that mainly 155A, 156F, and 157S chemerin isoforms are present in RA serum, which is different from the distribution in polycystic ovary syndrome, also showing increased total chemerin levels [ 79 ].…”
Section: Adipokines In Autoimmune Rheumatoid Arthritismentioning
confidence: 99%
“…Many studies evaluate several adipokines, contributing to the knowledge of cross-talking adipokine networks and relationships between adipokines as molecular mediators in RA. Systemic chemerin and visfatin were both increased in RA compared to healthy controls with chemerin, showing the highest specificity for RA [ 81 ]. On the cellular level, both visfatin and resistin alter the expression of miRNA in chondrocytes, leading to both reduced viability and increased apoptosis [ 30 ], thus showing the role of these adipokines in cartilage erosion.…”
Section: Adipokines In Autoimmune Rheumatoid Arthritismentioning
confidence: 99%
“…Etiopathogenesis for RA is obscure, it is a prototypic inflammatory disease that results from the interplay between genetic and environmental factors which alter the immunological homeostasis, wherein immunological stimulation and unwanted inflammation predominate. Inflammatory changes involving the synovium of the inflamed joints leading to pain, warmth, swelling, and stiffness that usually experienced early in the morning or after prolonged inactivity that lasts more than 30 min [3].…”
Section: Introductionmentioning
confidence: 99%